Pengaruh Waktu Tempuh dan Kualitas Layanan terhadap Kepuasan Pengguna Transportasi Laut di Pelabuhan Batam - IKHSAN, Muhammad (Politeknik Pelayaran Sumatera Barat, 2025)
This study investigates how passenger satisfaction in marine transportation at Batam Port is impacted by trip time and service quality. Given Indonesia's archipelagic terrain, sea transportation is an essential means of connectivity; nonetheless, enduring problems like delays, long trips, and subpar service continue to be a problem. This study uses a quantitative design using multiple linear regression to examine both simultaneous and partial impacts of the variables. It is based on the SERVQUAL model and Expectancy Disconfirmation Theory. A Likert-scale survey was used to collect data from 100 respondents. The results indicate that travel time and service quality significantly influence passenger satisfaction, with a determination coefficient of 83.9%. Although punctuality contributes to positive perceptions, service quality stands out as the dominant factor in shaping user experience and fostering long-term loyalty. The findings not only reinforce the theoretical relevance of combining EDT and SERVQUAL in maritime studies but also provide practical insights for port authorities and operators to enhance efficiency and service standards in order to strengthen competitiveness and passenger trust. Keywords: travel time, service quality, passenger satisfaction, maritime transport, Batam Port